Road to paradise - Simons, Paullina (London : Harper, 2008)
Love, passion and the road trip of a lifetime in this breathtaking new novel, perfect for all fans of Jodi Picoult. Two girls, an open road and a shiny yellow Mustang; it could have been the trip of a lifetime. But when Shelby and Gina pick up hitchhiker Candy Cane, their troubles have only just started. Inked with flowers and covered in piercings, they soon find out pink-haired Candy is on the run - for reasons so appalling they're almost unspeakable. They should have stuck to their no hitchhiker rule, but it's too late - and Gina and Shelby are drawn into a terrifying game of cat and mouse with no way out. As everything familiar is stripped away and morals are turned upside down, the question is this: how far will they go for a stranger?
National College of Business and Arts
Keywords: Women -- Travel -- United States -- Fiction; Thrillers (Fiction)